Algorytmy mrówkowe w pozyskiwaniu wiedzy z baz danych - Jakubczyc, Janina Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The knowledge discovery is still an open problem with many unsolved tasks. One of them is greediness of existing rule induction algorithms. Therefore there appear attempts enriching them with some global criterion that would control the search. One of such attempt is applying the mechanism of ant colony algorithms. The achievements of the study of ant colonies behaviour and of their selforganization capability is of interest to discover more universal unsupervised clustering algorithms. The anallysis of the implementations of different swarm intelligent mechanism is also the subject of this paper. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 159-174